(untitled) (London, 2003)
The International Symposia on Plant Lipids, the 15th of which was held in Okazaki, Japan, in May 12-17, 2002, is held every two years and is the only international meeting in this field. The almost 100 contributions from the symposium collected in this book represent the most up-to-date research results on plant lipids, including their structure, analysis, biosynthesis, regulation, physiological function, environmental aspects, and biotechnology, obtained world-wide during the last two years.
Keywords: Plant lipids